Macrophages - Prakash, Hridayesh (IntechOpen, 2021)
This book is a collection of chapters that discuss methodologies, resources, and technologies by dedicated authors. This book has addressed the significance of macrophages in infectious disease, tumor metabolism, and muscular disorders. All chapters have focused on the fate of differentiated macrophages and discussed molecular pathways that are important for the pathologic role of macrophages. I am confident that our readers will find this book useful in designing immune mediated strategies for managing various diseases that this book is based on.